SUATU APLIKASI DARI PENGGABUNGAN KONSEP STRAIT FUZZY SET DAN STRAIT SOFT SET - Putri, Fadya Zahraini; Nazra, Admi; Yanita, Yanita (LPPM Universitas Bina Bangsa, 2024)
This article presents an illustration of the application of combining the concepts of Strait Fuzzy Set and Strait Soft Set involving